Essentials of business statistics - Keller, Gerald; Warrack, Brian (Belmont, Calif. : Duxbury Press, 1994)
This book is about: Graphical descriptive methods; Numerical descriptive measures; Probability; Probability distributions; Sampling and sampling distributions; ...
Keywords: Commercial statistics; Commercial statistics